Using memory restructuring strategy to enhance dental behaviour - JACQUELINE E. PICKRELL, MASAHIRO HEIMA, PHILIP WEINSTEIN, TRILBY COOLIDGE, SUSAN E. COLDWELL, ERIK S (IAPD and Blackwell, 2007)
Fear and avoidance of the dentist are attributed primarily to classical conditioning associated with aversive treatment experiences in childhood.